Sustainability in German public procurement law: The current framework and legislative developments in the making - Wolters, Christopher Benedict; Ader, Ramona (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
This paper presents an overview of sustainability considerations in current German public procurement law. It highlights the existing scope and particularities in the implementation of EU public procurement law with regard to sustainability in Germany. Additionally, it briefly looks at how sustainability aspects are implemented in practice. Further, the article provides an outline of what is currently planned for the future as Germany intends to strengthen the aspect of sustainability in its public procurement through the so-called ‘public procurement transformation package’ (Vergabetransformationspaket).